Analysis of the Effect of Leadership Style, Work Motivation and Incentives on Sales Work Productivity at PT Dipo International Pahala Automotive Medan - Situmorang, Hotman; Yanti, Eli (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to find the effect of leadership style, work motivation and incentives on work productivity of PT Dipo Internasional Pahala Otomotif Medan. The number of samples in this study was 45 respondents. This study used quantitative data processed with SPSS 25.0 with a multiple linear regression model. The results of the study indicate that leadership style, work motivation and incentives partially and simultaneously have a positive and significant effect on work productivity of PT Dipo Internasional Pahala Otomotif Medan. The results of the t-test show that leadership style has a regression value of 0.412, t-count = 2.342 and significant = 0.000. Work Motivation has a regression value of 0.296 has a t-count = 2.027 and significant = 0.000. Incentives have a regression value of 0.055 and a t-count result of 1.987. The results of the determination coefficient test of 92.8% of work productivity can be explained and obtained from the variables of leadership style, work motivation and incentives, while the remaining 7.2% is influenced by other factors.